Alloploids’ synthesis in genus Nepeta L. and their cytological study (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Alloploid hybrids of Nepeta L. (allotriploid, pentaploid and hexaploid) are obtained by means of hybridization of three spesies: N. transcaucasica, N. grandiflora and N. cataria. Scheme of hybridization is given as well.
Keywords: N. transcaucasica, N. grandiflora, N. cataria, polyploidy, interspecific hybridization.